Impact of Transition Metal Layer Vacancy on the Structure and Performance of P2 Type Layered Sodium Cathode Material - Zhanadilov, Orynbay; Baiju, Sourav; Voronina, Natalia; Yu, Jun Ho; Kim, A-Yeon; Jung, Hun-Gi; Ihm, Kyuwook; Guillon, Olivier; Kaghazchi, Payam; Myung, Seung-Taek (Shanghai Jiao Tong University Press, 2024)
Vacancy in the transition metal layer of sodium cathode material induces the formation lone-pair electrons in the O 2p orbital.Material delivers more capacity from the oxygen redox validated by density functional calculation.Widened dominance of the OP4 phase without releasing O2 gas. This study explores the impact of introducing vacancy in the transition metal layer of rationally designed Na0.6[Ni0.3Ru0.3Mn0.4]O2 (NRM) cathode material. The incorporation of Ru, Ni, and vacancy enhances the structural stability during extensive cycling, increases the operation voltage, and induces a capacity increase while also activating oxygen redox, respectively, in Na0.7[Ni0.2VNi0.1Ru0.3Mn0.4]O2 (V-NRM) compound. Various analytical techniques including transmission electron microscopy, X-ray absorption near edge spectroscopy, operando X-ray diffraction, and operando differential electrochemical mass spectrometry are employed to assess changes in the average oxidation states and structural distortions. The results demonstrate that V-NRM exhibits higher capacity than NRM and maintains a moderate capacity retention of 81% after 100 cycles. Furthermore, the formation of additional lone-pair electrons in the O 2p orbital enables V-NRM to utilize more capacity from the oxygen redox validated by density functional calculation, leading to a widened dominance of the OP4 phase without releasing O2 gas. These findings offer valuable insights for the design of advanced high-capacity cathode materials with improved performance and sustainability in sodium-ion batteries.